2007
DOI: 10.1016/j.epsl.2007.05.026
|View full text |Cite
|
Sign up to set email alerts
|

The Lherz spinel lherzolite: Refertilized rather than pristine mantle

Abstract: Differentiation of the Earth's mantle and formation of continental and oceanic crust occur principally through partial melting and extraction of basaltic melt. Among the mantle rocks occurring at the Earth's surface, as tectonically-emplaced massifs, abyssal peridotites or xenoliths, the harzburgites (b 5% clinopyroxene) are widely considered as refractory mantle residues left after extraction of a basaltic component. In contrast, the most fertile lherzolites (15% clinopyroxene) are generally regarded as prist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
202
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(218 citation statements)
references
References 54 publications
(86 reference statements)
10
202
0
6
Order By: Relevance
“…Brunelli et al 2006;Le Roux et al 2007;Jean et al 2010) was not found in the studied Cpx harzburgite. Most of the Cpx 1 should have undergone the batch partial melting during the E2 event and, on this basis, we speculate that the Cpx 1 contents of our residual harzburgites were originally higher.…”
Section: The E2 Partial Melting Mantle Eventmentioning
confidence: 76%
“…Brunelli et al 2006;Le Roux et al 2007;Jean et al 2010) was not found in the studied Cpx harzburgite. Most of the Cpx 1 should have undergone the batch partial melting during the E2 event and, on this basis, we speculate that the Cpx 1 contents of our residual harzburgites were originally higher.…”
Section: The E2 Partial Melting Mantle Eventmentioning
confidence: 76%
“…The above reactions commonly involve the formation of an Al-rich phase, which, in the case of the Veria-Naousa pyroxenites, is spinel and have been described in Archean cratons [29,50] or subcontinental mantle regions such as the Lherz Mountains [51], Ronda [11,52,53] and Cabo Ortegal [45,54]. However, quite recently, it was documented that such reactions producing two pyroxenes after dissolution of olivine can also occur in abyssal pyroxenites [55].…”
Section: Origin Of Ol-orthopyroxenite and Websteritementioning
confidence: 99%
“…Nagy meglepetést okozott azonban, hogy az orogén övekhez kapcsolódó, alpi típusú perido titok ban ez fordítva is történhet, azaz a korábban kimerült harz burgitból, bazaltos olvadékkal történt reakció révén újra termé keny lherzolit lesz. Ezt legrészletesebben LE ROUX et al (2007) demonstrálták a francia Pireneusok Lherz (a lherzolit típuslelőhelye!) nevű tava közelében található peri dotitmasszívum vizsgálata során.…”
Section: úJratermékenyülés (Refertilization)unclassified